ANALISIS KELAYAKAN USAHATANI TOMAT (Solanum lycopersicum) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This Research aim to know technically about effort management tomato farming evaluated from technical aspect in Landasan Ulin Utara Liang Anggang Subdistrict Banjarbaru City South Kalimantan Province and to know about cost, acceptance, revenue and tomato farming Feasibility. Pursuant to result of seen from technical management tomato farming still relative modestly, this seen from farm processing until the conservancy. Production obtained from 15 tomato farmer responder with wide mean equal to 352.236,45kg/ farmer. Productivity 16.670,62 kg/ha or 16,6 ton/ha. Total Revenue with mean Rp. 93.929.720 per farmer . Total Earnings mean Rp. 49.463.569,44 per farmer. RCR Value tomato farming 1.78 competent so that to be feasible (RCR >1).